Detection of virulence and specific genes of Salmonella sp. indigenous from Jember, Indonesia - Ria Yulian; Erlia Narulita; MOCHAMMAD IQBAL; DESY ROCHMIYAH SARI; IRMA SURYANINGSIH; DIAN EKA APRILIA FITRIA NINGRUM (Society for Indonesian Biodiversity, 2020)
Abstract. Yulian R, Narulita E, Iqbal M, Rochmiyah D, Suryaningsih I, Ningrum DEAF. 2020. Detection of virulence and specific genes of Salmonella sp. indigenous from Jember, Indonesia. Biodiversitas 21: 2889-2892. The bacterium Salmonella sp. is the most common cause of foodborne infection in humans. It has the ability to invAde the host, Salmonellosis is highly influenced by the combination of chromosome and plasmid in which Salmonella Pathogenisitas Islands (SPIs) are the biggest gene in the chromosome that are responsible to build specific interaction between Salmonella and the host. This research performed detection on virulence and specific genes in the SPIs area using PCR method for two Salmonella spp. bacterial isolates originated from Jember which were KP2 and P21D. Seven pairs of primers including stn, fimA, spvR (virulence genes), invA, ivaB, spvC, and fliC-d (specific genes) were used. The result revealed that P21D bacteria containing 3 virulence genes i.e. stn, fimA, and spvR. Meanwhile, only two virulent genes stn, and spvR were present in KP2 bacteria. For the detection of specific genes, three genes invA, ivaB, and spvC were present while fliC-d genes were not detected. Only two, invA, and ivaB genes were detected in P21D bacteria, while spvC, and fliC-d were not detected.